2012
DOI: 10.1128/jb.06729-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Soybean Symbiont Sinorhizobium fredii HH103

Abstract: Sinorhizobium fredii HH103 is a fast-growing rhizobial strain that is able to nodulate legumes that develop determinate nodules, e.g., soybean, and legumes that form nodules of the indeterminate type. Here we present the genome of HH103, which consists of one chromosome and five plasmids with a total size of 7.22 Mb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 11 publications
1
34
0
Order By: Relevance
“…4), the tree showed that both the engA and tRNA arg genes were located on the main chromosome, except in the case of all sequenced S. meliloti strains (15 strains) and S. medicae WSM419 (16,43,44,54,55). Furthermore, both the engA and tRNA arg genes were located on the chromosome for Sinorhizobium fredii strains NGR234, USDA257, and HH103 (45)(46)(47) and nine recently sequenced Sinorhizobium strains (seven S. fredii strains, one Sinorhizobium sojae strain, and one Sinorhizobium sp. strain [56]).…”
Section: Figmentioning
confidence: 97%
See 1 more Smart Citation
“…4), the tree showed that both the engA and tRNA arg genes were located on the main chromosome, except in the case of all sequenced S. meliloti strains (15 strains) and S. medicae WSM419 (16,43,44,54,55). Furthermore, both the engA and tRNA arg genes were located on the chromosome for Sinorhizobium fredii strains NGR234, USDA257, and HH103 (45)(46)(47) and nine recently sequenced Sinorhizobium strains (seven S. fredii strains, one Sinorhizobium sojae strain, and one Sinorhizobium sp. strain [56]).…”
Section: Figmentioning
confidence: 97%
“…Genome sequences were downloaded from GenBank, and the corresponding accession numbers are as follows: AL591688.1 (S. meliloti 1021 chromosome) (41), AL591985.1 (S. meliloti 1021/pSymB) (15), CP001832.1 (S. meliloti SM11/pSmeSM11d) (42), CP002782.1 and CP002742.1 (S. meliloti AK83 chromosome 2 and S. meliloti BL225C/ pSINMEB02) (43), CP000738.1 and CP000739.1 (Sinorhizobium medicae WSM419 chromosome and pSMED01) (44), CP001389.1 and CP000874.1 (Sinorhizobium fredii NGR234 chromosome and pNGR234b) (45), NC_016812.1 (S. fredii HH103 chromosome) (46), and CP003563.1 (S. fredii USDA 257) (47).…”
Section: Methodsmentioning
confidence: 99%
“…Both strains are the best-studied model organisms with respect to host range. The analysis of the recently published complete genome of S. fredii NGR234 and the genome of the broad-host-range strain S. fredii HH103 suggested that these three strains share a high degree of synteny in their genomes (3,5,6). The complete genome sequence of USDA257 therefore significantly increases our knowledge of molecular mechanisms involved in the determination of host range in the interaction of plants with microbes.…”
mentioning
confidence: 97%
“…Man is also present in the genome of S. fredii strains (CCBAU 45436/ HH103) (17,40). However, the ptsI and ptsH mutants were not impaired in symbiotic performance in terms of the relative chlorophyll concentration and shoot dry weight of soybean ( Fig.…”
Section: Resultsmentioning
confidence: 99%